Topological Sustainability of Crop Water Requirements and Irrigation Scheduling of Some Main Crops Based on the Penman-Monteith Method - Waseem Asghar Khan; Jamshaid Ul Rahman; Mogtaba Mohammed; Ziyad Ali AlHussain; Murtada K. Elbashir (Journal of Chemistry)
The following method was used to apply the topology of the current study of evapotranspiration ETo, net irrigation demand, irrigation schedules, and total effective rain fall of different crop models: using the Food and Agriculture Organization's (FAO) CROPWAT 8.0 standard software and the CLIMWAT 2.0 tool and the FAO-56 Penman-Monteith approach to examine the variable topology of evapotranspiration ETo. Due to high temperatures in summer with an annual mean of 6.33 mm/day, the topological demonstration of reference evapotranspiration (ETo) increases from 2.84 mm/day in January to a maximum of 9.61 mm/day in July. Effective rainfall fluctuates from 0 mm to 53.4 mm. Total irrigation topological indices requirements were 308.3 mm/dec, 335.9 mm/dec, 343.6 mm/dec, 853 mm/dec, and 1479.6 mm/dec for barley, wheat, maize, rice, and citrus, respectively. The physical topological indices due to low demand in winter and high demand in summer, the total net irrigation, and gross irrigation for clay loamy soils for wheat (210.6 mm and 147.4 mm), barley (176.6 mm and 123.6 mm), citrus (204.5 mm and 143.2 mm), and maize (163.9 mm and 114.7 mm), but not for rice. This topology demonstrates that wheat has 4, barley has 4, citrus has 12, maize has 4, and rice crop has 12 irrigation schedules in a year.